Cáncer tiroideo en niños: Terapia y seguimiento en carcinoma bien diferenciado. - SÁNCHEZ-VÁSQUEZ, Raúl; SÁNCHEZ ROBLES, Raúl; MUÑOZ CARBAJAL, Pedro; MACEDA NUÑEZ, Walter; TREFOGLI REY, Pablo; DIEGUEZ, Julio; CABELLO MORALES, Emilio; MEDINA DELGADO, Mercedes del Pilar (Revista Médica Herediana, 2015)
We report two cases of well differentiated thyroid carcinoma (DTC) in two girls who showed their first symptoms at 4 years 6 months and 7 years 2 months. Both underwent total thyroidectomy and removal of metastatic lymph nodes. In the first case pathology informed a mixed DTC (papillar/follicular). In the first case we discuss the difficulties that may arise due to the unspecified signs and symptoms that led to an initial diagnosis of goiter and thyroiditis. We emphasize the importance of age, sex, the presence of cervical adenopathy and associated hoarness in order to establish the diagnosis of DTC. In the second case we point out the diagnostic importance of the progressive growth of the cold thyroid nodule. We review the different surgical approaches of resection supporting the advantages of the total over the subtotal thyroidectomy we had done on our patients. We analyze the concepts of uni and multifocality of DTC taking into consideration the possibility of death even among low risk patients. We discuss the higher frequency of relapse in patients who were not treated with radioactive iodine (I-131) or who were given low doses of iodine. We establish the advantages of post-surgical ablation with high doses (100 to 150 mCi) of I-131, based on the longer patient survival and minimum recurrences. The first studied case has had 15 years 9 month of survival with no recurrences up to date. The second studied case has had 6 years 10 month of survival, also with no recurrences up to date. We also emphasize the importance of an adequate suppressive hormone dose (200 mcg day of thyroxine) based on the concept of the TSH dependance of this tumors. We conclude mentioning that the prognosis depends an adequate follow up schedule.